2018
DOI: 10.1002/jlb.2mir0917-377r
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for coinhibitory receptors/checkpoint proteins in the immunopathology of sepsis

Abstract: Coinhibitory molecules, such as PD-1, CTLA-4, 2B4, and BTLA, are an important new family of mediators in the pathophysiology of severe bacterial and/or fungal infection, as well as the combined insults of shock and sepsis. Further, the expression of these molecules may serve as indicators of the immune status of the septic individual. Using PD-1:PD-L as an example, we discuss in this review how such checkpoint molecules may affect the host response to infection by mediating the balance between effective immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 131 publications
(272 reference statements)
0
30
0
Order By: Relevance
“…In previous studies, our laboratory found SHP1 negatively modulated PD-L1-dependent regulation of Treg cell function during the resolution of shock/sepsis-induced lung injury (Tang et al 2015 ). As a component of co-inhibitory receptor signaling, via a number of B-7 checkpoint protein receptor family members, e.g., PD-1, BTLA, etc., SHP1 and/or SHP2 recruitment can serve to alter/suppress T-cell as well as select monocyte/macrophage function(s) in a number of conditions, tumor clearance, viral challenge, wound healing as well as Hem/CLP (Fallon et al 2018 ). Thus, it would not be suprising if SHP2 blockade also had effects on such cells and/or functions, especially, if used in a protracted/long-term fashion (not acutely as done here).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, our laboratory found SHP1 negatively modulated PD-L1-dependent regulation of Treg cell function during the resolution of shock/sepsis-induced lung injury (Tang et al 2015 ). As a component of co-inhibitory receptor signaling, via a number of B-7 checkpoint protein receptor family members, e.g., PD-1, BTLA, etc., SHP1 and/or SHP2 recruitment can serve to alter/suppress T-cell as well as select monocyte/macrophage function(s) in a number of conditions, tumor clearance, viral challenge, wound healing as well as Hem/CLP (Fallon et al 2018 ). Thus, it would not be suprising if SHP2 blockade also had effects on such cells and/or functions, especially, if used in a protracted/long-term fashion (not acutely as done here).…”
Section: Discussionmentioning
confidence: 99%
“…However, some researchers had identified that the predominant immunosuppressed characteristic was that the monocytes cocommunicate with T cells in the sepsis process [10]. The monocytes, a kind of antigen-presenting cells (APC), acted as instigators of T cell suppression in adaptive response by mediating the expression of inhibitory coreceptors such as programmed cell death protein 1 (PD-1) and cytotoxic T lymphocyte-associated protein 4 (CTLA4) [10,11]. The researches of Avendano-Ortiz et al [12] and Shalova et al [13] showed that hypoxia-inducible factor-1α (HIF-1α) regulated functional reprogramming of monocytes in sepsis to suppress T cells with inhibitory coreceptors, cytokines, and chemokines.…”
Section: Introductionmentioning
confidence: 99%
“…PD-1 and CTLA-4 are suggested to play a key role in the host response over the course of sepsis 16 , 17 ; these proteins function as concomitant inhibitory receptors within the process of T cell activation and proliferation 18 . While antigen-presenting cells (APC), such as macrophages, dendritic cells or monocytes, present antigens from foreign pathogenic sources on MHC II towards T cell receptor-expressing lymphocytes, costimulatory and coinhibitory cascades occur simultaneously (e.g., costimulatory receptors CD40 and CD28; coinhibitory receptors PD-1 and CTLA-4) 19 . In particular, CTLA-4 is a T cell surface protein that competes with CD28 for binding to CD80 and CD86 on APCs 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…While antigen-presenting cells (APC), such as macrophages, dendritic cells or monocytes, present antigens from foreign pathogenic sources on MHC II towards T cell receptor-expressing lymphocytes, costimulatory and coinhibitory cascades occur simultaneously (e.g., costimulatory receptors CD40 and CD28; coinhibitory receptors PD-1 and CTLA-4) 19 . In particular, CTLA-4 is a T cell surface protein that competes with CD28 for binding to CD80 and CD86 on APCs 19 , 20 . Thus, overexpression of CTLA-4 downregulates the activation and proliferation of T cells and therefore has an inhibitory effect on the host immune reaction, preventing an overreaction of the immune system 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation